Hybrid energy harvesting of piezoelectric and electromagnetic using vibration excitation of bimorph cantilever beam - Nik Nurul Husna, Muhmed Razali (2019)
Harvesting energy is the technique for accumulating energy from the surrounding environment and transforming it into electricity. Instead, the evolution of low power electronics, dependencies on battery as a power source that can decrease the lifespan and function capability. Thus, many researchers are finding that energy harvesting method can increase the power output depending on the geometry and material applied. The main objective is to develop energy harvesting of a piezoelectric and electromagnetic system based on vibration excitation. In this project, the implementation of harvesting energy from two technologies to form a hybrid energy harvester system was analyzed. These two technologies involve the piezoelectric harvesting energy and the electromagnetic harvesting energy. A finite element model was developed using the Ansys software with the harmonic analysis solver for initial beam and response surface optimization for optimum beam. Both power output generated by the electromagnetic and the piezoelectric is then combined to form one unit of energy. The power harvesting circuit was developed to store the power output instead to use the battery as power source and compared the AC and DC power output using a shaker. Thus, shaker was used as a modal testing to validate the analytical result. Further, it was found that the initial beam result of analytical was validated with experiment result with 8% error for voltage and the power harvesting of AC source was highest compare to DC source. Others, the optimal beam was validated that voltage has 3.32% error while power has 10.86% error between analytical and experiment results. Normalized Power Density (NPD) results of the optimal beam at 13.927 kgs/m3 are comparable with other literature also can be used in energy harvesting system for vibration application. Additionally, the efforts can be made towards decreasing the size of this harvester from 36.5 mm x 19.05 mm to 35 mm x 10.24 mm while still maintaining a interested resonant frequency and power output. Nevertheless, the optimum beam has minimized size instead of has higher normalized power density was generated of this project. The outcome of this work could be effectively used to improve the better lifespan and function capability performance for generating AC-DC sources.